Patterns of reasons for retirement in Olympic athletes from Switzerland: a person-oriented study - Schmid, M. J.; De Crom, L.; Conzelmann, A.; Schmid, J. (International Journal of Sport and Exercise Psychology, 2025)
The reasons for the end of a career in elite sport have long been a major topic in sport psychology. Although the literature repeatedly emphasises that retirement decisions are multi-causal and individual-specific, quantitative studies have hardly taken this into account methodologically. Therefore, the aim of this study was to identify and validate patterns of reasons for retirement among elite athletes, to explore associations between these patterns and the former athletes` current life situation (post-retirement). Using a quantitative approach, we surveyed 341 former athletes (Mage = 47.16 years, SD = 7.72; 32.9% female, 67.1% male) who represented Switzerland at the Olympic Games about their reasons for retirement, the characteristics of their retirement, and their life situation post-retirement (e.g., health, socio-economic status). A person-oriented analysis revealed six clusters of reasons for retirement: (1) family- and finance-related termination, (2) work- and goal-related termination, (3) environment-related termination, (4) family- and goal-related termination, (5) health-related termination, (6) performance-related termination. The cluster solution was validated with transition characteristics. Furthermore, clusters showed differences in various aspects of post-retirement life: Athletes with a mainly health-related termination reported significantly more sport-related health problems compared to the other clusters. In contrast, athletes with a work- and goal-related termination tended to have higher socioeconomic status, while those with a family- and finance-related termination tended to have more children. These findings highlight the need to understand reasons for retirement in order to design targeted interventions and support smoother transitions, for example, by offering long-term health support to athletes retiring for health reasons.